(untitled) (Manila, 1994)
Rice research seeks to generate knowledge and technologies that bring improvement in the welfare of rice-dependent households. In pursuit of this goal, individuals and institutions seek partnerships with expectations of increased effectiveness and efficiency. This volume documents the achievements of a quarter century of partnership between Vietnam and the International Rice Research Institute (IRRI) in rice research and identifies some of the remaining challenges and opportunities.
Keywords: Rice,Rice; Research; Vietnam,Vietnam